Analysis of an Awareness Program of Cyber Security in PIET, Jaipur: A Systematic Survey - Suman Jain; Siddharth Joshi (International Journal of Information Security Engineering, 2024)
This paper presents an analysis on what the students and the new generation think an out cyber security after learning about cyber-crimes and security in an awareness program. Our knowledge of technology has dramatically increased in the past five decades, as a result it also gave us a new type of threat, cyber-threats. Through smartphones and computers, life has become easy both for individuals and big organizations. Therefore, we must learn how to be cyber aware. The newer generation certainly knows about the internet risks but according to a survey conducted by Ernst & Young LLP, the newer generation which is born and lives in cyber era is less concerned about cyber security on their work devices than the previous one. Their overconfidence in their ability to avoid deception could be one factor behind this. “Anybody can be scammed” said Ashton Bingham, a cyber security expert from Trilogy Media YouTube channel, on a wired interview. To find the change in vision towards security, firstly, we needed to give students an attention towards cyber-crimes and protections so that they can be aware of all type of scams and threats and how to protect themselves from these. Secondly, we needed to collect data of students about how aware they are. Our research does not include the “fear appeal” of cyber security; instead, it includes cyber awareness as an essential duty of an organization or an individual to protect themselves and their employees or relatives from getting scammed. We are including our survey results here as it shows how an awareness program or campaign makes students more aware towards cyber security. We collected data from 262 students who attended the cyber security campaign. Our article also includes the survey from Arwa A. Al Shamsi for comparison of the campaign impact on the students.
Keywords: Awareness; Cyber security; Students; cyber frauds; threats